Microorganisms and Biological Pest Control: An Analysis Based on a Bibliometric Review - Hernández-Rosas, Francisco; Figueroa-Rodríguez, Katia A.; García-Pacheco, Luis A.; Velasco-Velasco, Joel; Sangerman-Jarquín, Dora M. (Agronomy (Basel), 2020)
The use of microorganisms for biological pest control as biological control agents (BCAs) and biopesticides was developed worldwide in the 1960s. Despite the abundance of reviews published on this topic, no meta-analysis using bibliometric tools has been published. The objective of this study was to determine patterns of research on microorganisms for the biological control of pests, based on publications available in the SCOPUS® database. The data were obtained from the Elsevier® Scopus meta-database using the search terms “biological pest control” and “microorganism” (title, abstract, and keywords). The main publications were identified, along with the journals, countries, and institutions that have published on the subject. The data were analyzed with VOSviewer to determine the co-occurrence of terms, and four maps were generated. The results show two phases in the scientific research on the subject: The first is the characterization of biological control agents, and the second is focused on the commercial development of biopesticides and biological control agents. The most recent research emphasizes the discovery of new species and strains that have commercial potential, with an emphasis on genetic engineering and biotechnology.